(untitled) - Geda Anusha; Yugandhar Samireddypalle; Ranjith Kumar Vulchi; Sagar Dembla; Pavithira Annamalai; Sabarinath Eada; Amitha Vikrama K S (Asian Journal of Medical Radiological Research, 2020)
Background: The incidence of end stage renal disease is on the rise and most of these patients are undergoing dialysis either through tunnelled/non tunnelled dialysis catheters or through arteriovenous fistulas/grafts. The dialysis grafts and fistulas have limited durability of about 3 years and are more prone for thrombosis and stenosis. Catheter directed interventions are successful in establishing flow in most of the thrombosed fistulas, but require dedicated Cath lab and tertiary care centre. Needle directed thrombolysis is a novel economical, safe technique for thrombolysis of dialysis fistulas and grafts. The aim of the studt is to review the technique, safety, efficacy of needle directed pulse spray pharmacomechanical thrombolysis of dialysis fistulas and grafts with short term follow up. Subjects and Methods: This was a prospective observational study done in department of Radio diagnosis, Narayana medical college, Nellore. Selectively 25 patients with thrombosed AV fistulas were referred from nephrology OPD for needle directed thrombolysis to our department from December 2018 to May 2019. The procedure was performed on OPD basis in ultrasound procedure room. Regular Doppler follow up of patients is done up to 6 months. Results: Out of twenty five cases about seventeen cases (68%) were successful in achieving adequate recanalization in single session. four cases (16%) required repeat sessions of thrombolysis and were successful in second attempt. In four cases (16%) there was failure in attaining adequate recanalization due to marked multisegment attenuation/flow limiting stenosis of the draining vein. Conclusion: Needle directed Pulse spray pharmacomechanical thrombolysis is a novel technique, which can be done bedside, under portable ultrasound guidance and is an economical procedure as no intervention hardware is required. Continuous monitoring allows procedure to be stopped at the earliest once there is optimal recanalization, minimizing the systemic side effects of thrombolytic agents.